ACHIEVING PUBLIC SCHOOLS - Abowitz, Kathleen Knight (Educational theory, 2011)
Public schools are functionally provided through structural arrangements such as government funding, but public schools are achieved in substance, in part, through local governance. In this essay, Kathleen Knight Abowitz explains the bifocal nature of achieving public schools; that is, that schools are both subject to the unitary Public compact of constitutional principles as well as to the more local engagements with multiple publics. Knight Abowitz sketches this bifocal nature, exploring both the unitary ideal and its parameters, as well as the less understood forms of multiple, organic publics that come into being in response to localized problems in schools or districts. These publics often fail to realize their potential in the development of increased capacity for enhanced teaching and learning. The essay ultimately points to a practical application: that educational leadership of all types, and with some very specific kinds of habits and skills, is needed to help achieve public schools.